Genetic and Functional Analysis of the Chromosome-Encoded Carbapenem-Hydrolyzing Oxacillinase OXA-40 of Acinetobacter baumannii - Héritier, Claire (American Society for Microbiology, 2003)
Clinical isolate Acinetobacter baumannii CLA-1 was resistant to a series of antibiotic molecules, including carbapenems. Cloning and expression of the β-lactamase gene content of this isolate in Escherichia coli DH10B identified a chromosome-encoded oxacillinase, OXA-40, that differed by one or two amino acid changes from OXA-24, -25, and -26 and an AmpC-type cephalosporinase. The OXA-40 β-lactamase had a mainly narrow-spectrum hydrolytic profile, but it included ceftazidime and imipenem. Its activity was resistant to inhibition by clavulanic acid, tazobactam, sulbactam, and, like most of the other carbapenem-hydrolyzing oxacillinases, NaCl. OXA-40 had an FGN triad replacing a YGN motif at class D β-lactamase (DBL) positions 144 to 146. Site-directed DNA mutagenesis leading to a Phe-to-Tyr change at DBL position 144 in OXA-40 gave a mutant enzyme with increased hydrolytic activity against most β-lactams, including imipenem. Conversely, with a gene encoding the narrow-spectrum oxacillinase OXA-1 as the template, a nucleotide substitution leading to a Tyr-to-Phe change in the YGN motif of OXA-1 gave a mutant enzyme with decreased hydrolytic activity without an increase in carbapenem-hydrolyzing activity. Thus, the Phe residue in the FGN motif was not associated with carbapenem-hydrolyzing activity by itself but instead was associated with weak overall hydrolytic activity. Finally, this Phe residue in OXA-40 explained resistance to inhibition by NaCl whereas a Tyr residue in motif YGN was related to susceptibility to NaCl.